Claudin11 promoter hypermethylation is frequent in malignant melanoma of the skin, but uncommon in nevus cell nevi - Walesch, Sara; Richter, Antje M.; Helmbold, Peter; Dammann, Reinhard H. (Cancers, 2015)
Epigenetic inactivation of tumor-related genes is an important characteristic in the pathology of human cancers, including melanomagenesis. We analyzed the epigenetic inactivation of Claudin 11 (CLDN11) in malignant melanoma (MM) of the skin, including six melanoma cell lines, 39 primary melanoma, 41 metastases of MM and 52 nevus cell nevi (NCN). CLDN11 promoter hypermethylation was found in 19 out of 39 (49%) of the primary MM and in 21 out of 41 (51%) of the MM metastases, but only in eight out of 52 (15%) of NCN (p = 0.001 and p = 0.0003, respectively). Moreover, a significant increase in the methylation level of CLDN11 from primary melanomas to MM metastases was revealed (p = 0.003). Methylation of CLDN11 was significantly more frequent in skin metastases (79%) compared to brain metastases (31%; p = 0.007). CLDN11 methylation was also found in five out of six MM cell lines (83%) and its promoter hypermethylation correlated with a reduced expression. Treatment of MM cell lines with a DNA methylation inhibitor reactivated CLDN11 transcription by its promoter demethylation. In summary, CLDN11 proved to be an epigenetically inactivated tumor related gene in melanomagenesis, and analysis of CLDN11 methylation level represents a potential tool for assisting in the discrimination between malignant melanoma and nevus cell nevi.
Gesehen am 26.06.2020